Pelatihan Kepemimpinan Pengurus OSIS Di MA Al Hidayah Semarang - Sutaat Sutaat; Dyah Purwaningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Leadership training for Intra-School Student Organization (OSIS) administrators at MA Al Hidayah Semarang to develop leadership skills in students who are responsible for leading organizations at school. This can help them learn concepts, and effective practices in the context of leadership. The methods used in this training are situation analysis, preparation, implementation, and evaluation. During the training, participants engage in various activities and exercises that involve understanding leadership concepts, effective communication, and organizational strategy. They learn how to communicate well with their peers, organize activities at school, motivate other students to participate, and make the right decisions and the importance of leadership ethics, such as integrity, responsibility, honesty, and a positive attitude. So that they can be good role models for other students and build a positive image of the OSIS at school. At the end of the training, participants are allowed to apply their new leadership skills through the OSIS work program. This service aims to provide practical experience to students in managing work programs, collaborating with members, working with teams, and facing organizational challenges that may arise. Leadership training aims to strengthen their leadership skills and make a real contribution to school development. It is hoped that this service can provide a strong foundation for them to become effective leaders and can have a positive impact on improving their school and community.